PERAN SUPERVISOR KEPALA SEKOLAH DASAR DALAM MENINGKATKAN KUALITAS PEMBELAJARAN AGAMA ISLAM DI SDN BINANGUN 1 SINGGAHAN TUBAN TAHUN PELAJARAN 2021/2022 - Hidayati, Ninik; Hakim, Nurul; Fauzi, Ali (Program Studi PGMI Fakultas Tarbiyah Institut Agama Islam Nahdlatul Ulama Tuban, 2022)
The Supervision Role of the SD Head in providing quality learning for Islamic Religion SD Binangun 1 SinggahanTuban. Based on the background of the problem, this research is expected to provide answers to the formulation of the problem (1) How is the supervision carried out by the Head of SD Binangun 1 Singgahan? (2) What is the supervisory role of the madrasah head in improving the quality of Islamic learning at Binangun 1 Singgahan Elementary School in the 2021/2022 Academic Year? This research is a qualitative research. From the results of this study it was found that (1) The implementation of the supervision of the elementary school head in Islamic learning at Binangun 1 Singgahan Elementary School includes: first, the process of supervision, supervision is carried out 2 times in one semester. Second, monitoring the readiness of learning, before the teacher starts learning the head of the madrasa checks the learning tools. (2) The supervisory role of the SD head to improve the quality of learning Islamic religion at Binangun 1 Singgahan Elementary School cannot be separated from the role of the madrasa head in carrying out his duties as a supervisor and the role of a teacher as a learning implementer.